Wooden ladle from the collection of the National Art Museum of the Republic of Belarus: to the discussion about attribution - Skvarcheuski, Dzmitry V.; Butov, Ilya S. (Journal of the Belarusian State University. History, 2025)
This publication is devoted to the attribution of a wooden ladle with twelve anthropomorphic, zoomorphic and ornithomorphic images from the collection of the National Art Museum of the Republic of Belarus. The authors attribute its manufacture to the period of the 15th–17th century on the basis of the analysis of the ladle shape. The artifact has no direct analogues in terms of shape and stylistics of painting and cannot be attributed to the types of wooden ladles known in the literature. According to the authors, the versions about its imported origin (from the territory of Russia) are not justified. The authors believe that it was made in Belarus. The secondary, now lost, polychrome painting was presumably applied to the ladle in the second half of the 17th – first half of the 18th century. The authors have introduced previously unpublished archival material into the research.
Keywords: ladle; museum object; iconography; applied arts